Delivery of CANTAB assessments across diverse health systems: Developing topics. (7th December 2020) - Baker, Elizabeth; Dente, Pasquale; Backx, Rosa; Lowther, Millie; Cotter, Jack; Cormack, Francesca K; Barnett, Jenny
Abstract: Background: Assessment of cognitive function is an important component of differential diagnosis in Alzheimer's disease and dementia and is critical to characterising the impact of the disease. Objective assessment of function provides real world evidence for assessing effectiveness of current standards of care, and evaluating interventions designed to improve outcomes. However, sensitive, reliable tools for administering standardised tests at scale have been lacking to date. Method: Digital tools, providing near‐patient assessments in the community or at home are one way to meet the demands of patient characterisation across a range of resource settings. Cambridge Neuropsychological Automated Test Battery (CANTAB) is a set of 25 computerised assessments designed to assess cognition across a broad range of domains relevant to neurological and psychiatric conditions. A number of tests from this battery have been integrated into medical device software to assess the impact of neurological and neurodegenerative disease. These tools have been deployed in community, primary and secondary health care settings in relatively resource‐rich healthcare systems (primarily UK and US). We are exploring whether such an approach can be generalised to a lower‐middle income countries/South Asia. Result: We will present performance of 4000 healthy participants recruited across nine regions of India on CANTAB assessments including performance on episodic memory (Paired Associates Learning (PAL)), working memory (Spatial Working Memory (SWM)) and attention (Matching to Sample (MTS)). Evidence from this study supports the suitability of our platform for delivering cognitive assessments in health care systems outside the UK. We will contrast performance of healthy participants on PAL and SWM with recent normative data collections across the UK and US; demonstrating similarity of performance and the effectiveness of assessment platforms. The demographic diversity of these normative collections supports the need to partner these tools with appropriate recruitment and operational initiatives to ensure accessibility. Conclusion: We will reflect on how this evidence guides our current and future plans for making scientifically robust cognitive assessment tools globally available, both for increasing access to treatment, but also in the context of basic research and drug development.